The fundamental matrix: Theory, algorithms, and stability analysis - Luong, Quan-Tuan; Faugeras, Olivier D. (International journal of computer vision, 1996)
The geometry of a pair of cameras, i.e., a stereo rig, is analyzed in detail. The projective nature of the correspondence problem in stereo is clarified and the epipolar geometry is summarized in one 3x3 matrix of rank 2 which is called the Fundamental matrix. The Fundamental matrix is then estimated from point correspondences. Several methods of estimation are analyzed theoretically and compared using synthetic and real data. The importance of the Fundamental matrix in future applications of three-dimensional Computer Vision is also emphasized.